2021
DOI: 10.1002/erv.2836
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive–compulsive symptoms in female patients with an eating disorder with or without impulsive non‐suicidal self‐injury

Abstract: Background and Aims In the present study, we investigated differences in obsessive–compulsive (OC) symptoms in patients with an eating disorder (ED) with or without recent/lifetime impulsive non‐suicidal self‐injury (NSSI). We included 429 female inpatients with an ED, of whom 31.9% engaged in recent impulsive NSSI and 56.4% in lifetime impulsive NSSI. Materials They filled out the Eating Disorder Evaluation Scale, the Self‐Injury Questionnaire‐Treatment Related and the Padua Inventory‐Revised (OC symptoms). M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 15 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…A recent meta-analysis summarizing research on NSSI in EDs quantified lifetime NSSI prevalence as 27% across different age groups and treatment settings ([ 20 ]; 29 studies). Specifically, in adult in- and outpatients with AN-R, AN-BP, and BN, approximately half engaged in NSSI [ 28 , 29 ]. Concerning minors suffering from AN and BN, only four studies focused on lifetime NSSI.…”
Section: Lifetime Prevalence Of Nonsuicidal Self-injury In Anorexia N...mentioning
confidence: 99%
See 2 more Smart Citations
“…A recent meta-analysis summarizing research on NSSI in EDs quantified lifetime NSSI prevalence as 27% across different age groups and treatment settings ([ 20 ]; 29 studies). Specifically, in adult in- and outpatients with AN-R, AN-BP, and BN, approximately half engaged in NSSI [ 28 , 29 ]. Concerning minors suffering from AN and BN, only four studies focused on lifetime NSSI.…”
Section: Lifetime Prevalence Of Nonsuicidal Self-injury In Anorexia N...mentioning
confidence: 99%
“…Overall, the broad range of lifetime NSSI varying between 15 and 88% could result from different treatment settings, populations, and measurements based on diverse NSSI conceptualizations [ 34 36 ]. Higher NSSI prevalence in binge-purge EDs [ 29 , 37 ] could be explained by affect regulation for the increased impulsivity and negative affect in BN and AN-BP vs. AN-R [ 38 , 39 ]. Taken together, only four studies were identified focusing on a history of NSSI in adolescents and adults with EDs.…”
Section: Lifetime Prevalence Of Nonsuicidal Self-injury In Anorexia N...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors have addressed the interrelationships between eating disorders and self-harm (Nitkowski & Petermann, 2011;Claes et al, 2007;2021, Depestele et al, 2015Sarbach-Andrae et al, 2007, Fialová & Krch, 2012. Eating disorders on their own very often induce self-harming behaviour (Hawton et al 2002;Dougherty et al, 2009;Fliege et al, 2009).…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…According to Kriegelová (2008), frequent and incorrect criticism from the parent or other close person results in fear of the parent, which according to our findings is related to self-harm and is one of the symptoms of eating disorders. Furthermore, it is an insufficient and disproportionately emotionally adequate response to manifestations in childhood, weak provision of space for the development of autonomy, great effort from parents to control the child and exposure to severe and stressful events such as death of a relative or loved one, accident or bullying of a child in school, internet, and another environment (Kriegelová, 2008, Claes et al, 2021. According to Sutton (1999), the factors influencing intentional self-harm are long-term child abuse, developing problems with one's own identity, feelings of sadness, frequent loneliness, or the occurrence of lacrimosity, and others.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%